Futureproofing against shock: Institutional responses to terrorist risk in London, 1990–2020. (August 2021) - Coaffee, Jon
Abstract: Employing an institutionalist approach to governance, and engaging with recent scholarship on organisational resilience and scalar politics, this paper focuses upon institutional reactions to terrorism in London between 1990 and 2020 and explores the mechanisms through which responses to disruption occurred. Empirically, this applied paper tracks specific emergency processes, governance assemblages and policy mechanisms that have been enacted in London in response to terrorism. More specifically, it tracks changes in the institutional dynamics involved in the reorganisation of traditional governance apparatus, the mobilisation of adaptive capacity, and the generation of multi-stakeholder visions for futureproofing against terrorist attack. Such institutional changes are explored through three vignettes of responses to terrorist incidents: against financial targets in the 1990s; in relation the risk of attack after 9/11 and in preparation for securing the 2012 Olympics; and in response to recent attacks against crowded places since 2012. This paper illuminates how institutional responses to terrorism have evolved from a focus upon small specialist networks that dealt just with terrorism, to much larger multi-institutional, multi-scalar and multihazard responses to, and preparations for, complex emergencies that cut across numerous administrative jurisdictions. The paper concludes by posing wider questions about optimal institutional form(s) required for responding to future shocks. Highlights: London's institutional responses to terrorism are analysed over a 30-year period. London's preparedness for acts of terrorism is still a work in progress. Through strategic policies London has increasingly institutionalised resilience across municipal authorities and emergency stakeholders. London is increasingly active in promoting learning and knowledge exchange for global counter-terrorism. Through partnership approaches to governance, cities can become more resilient to terrorism and others disruptive shocks.